DAMPAK MULTIGANDA RENCANA INDUK PEMBANGUNAN KEPARIWISATAAN DAERAH (RIPPARDA) TERHADAP KEPARIWISATAAN DI DAERAH ISTIMEWA YOGYAKARTA - Prakoso, Aditha Agung (Kepariwisataan: Jurnal Ilmiah, 2016)
Nowadays, Daerah Istimewa Yogyakarta is announced as one of tourism destination in Indonesia. It is confirmed that Daerah Istimewa Yogyakarta in Regulation of Government No 50 of Government No 50 Year 2011 is belong to 50 national tourism destinations as known as National Tourism Destination Borobudur – Yogyakarta and its surrounding area. To accomplish The Act No 10 Year 2009 on Tourism and Regulation of Government No 50 Year 2011 on Grand Strategy of National Tourism Development, so Daerah Istimewa Yogyakarta composed Grand Strategy of Regional Tourism Development that called Regulation of Regional Government No 1 Year 2012 on Grand Strategy of Regional Tourism Development Provence Daerah Istimewa Yogyakarta. It is expected to give positive multiplier effect for Daerah Istimewa Yogyakarta community. Keywords: tourism destination, multiplier effect, grand strategy of national tourism development, tourism planning